Efficiency and the Fiscal Gap in Federal Systems - Robin W. Boadway; Michael Keen (Queen's University, Department of Economics, 1994)
This paper investigates the efficiency argument for a vertical fiscal gap in a federation using a simple model of a central government and several identical states. Each level provides a public good to residents within its jurisdiction and finances it by taxing labour income and rents. If labour supply is fixed, there need not be a fiscal gap even if households are perfectly mobile. With variable labour supply, however, decentralized decision-making by the states will generally be inefficient because states' tax policies will affect not only their own revenues but also those of the federal government. If the federal government chooses its budgetary policy first and the states take this policy as given, federal policies can be chosen to replicate the second-best optimum. Moreover, with or without mobile households, second-best optimal federal policy involves negative federal labour tax rates and can plausibly also require a negative fiscal gap, with transfers going from the states to the federal government. Thus, on efficiency grounds, there can be no presumption that inter-governmental transfers should go from higher levels of government to lower.
Keywords: H73; H77; H41; 330; Fiscal Gap; Fiscal Federalism